SUSTAINABLE CONSTRUCTION SITE: PLACE OF KNOWLEDGE AND TRANSFORMATION - Violano, Antonella; Cirafici, Alessandra; Spuria, Letteria; Melchiorre, Lucia (BDC. Bollettino Del Centro Calza Bini, 2016)
Contemporary city, place of social identity and historical memory, is cyclically affected by the presence of construction sites that hinder the usual physical and perceptive fruition of its public spaces and monuments. The necessity is to use these places of transformation as places of experimentation and spread of knowledge, producing a new image of the city and its monuments in order to allow the transmission of the meaning and value of the transforming physical space toward the future. The research work focuses on these issues and here we present some critical insights. The feasible answers are part of valorization plans, construction solutions and design guidelines, which aim to promote a transformation process, that can really be defined “sustainable” by exploiting communication strategies, which transform a traditional construction site in a “construction site of knowledge”. Keywords: construction site, environmental impact, social impact